TOLERÂNCIA DE PERDAS DE SOLO NA BACIA DO RIO ITIQUIRA, MATO GROSSO, BRASIL - Oka-Fiori, Chisato; Fiori, Alberto Pio; Hasui, Yociteru (Boletim Paranaense de Geociências, 2004)
Com a finalidade de avaliar a dinâmica ambiental no ecossistema da bacia de Itiquira e identificar área com problemas especiais, notadamente no que diz respeito à inadequada utilização do solo, realizou-se a análise da erosão laminar na bacia do rio Itiquira, na porção que se estende dos afluentes da sua cabeceira, no leste da chapada Correntes / Itiquira, até a escarpa da serra de São Jerônimo, num total de 5.361 km2. A erosão laminar foi avaliada pelo emprego da Equação Universal de Perdas de Solo (EUPS) para os anos de 1966, 1985 e 1996. Como conseqüência do rápido processo de ocupação antrópica, acelerou-se o processo de erosão do solo. Em 1966 havia uma perda média de 0,37 t/ha.ano, valor que passa a 3,28 t/ha.ano em 1985 e para 3,10 t/ha.ano em 1996. No período de 1985 a 1996 houve pequena desaceleração do processo erosivo em correspondência a um aumento nas áreas de pastagem. Escassos dados de hidrossedimentologia mostram a produção de sedimentos do rio Itiquira entre 1,39 a 2,04 t/ha.ano para o ano de 1988, em boa concordância com os resultados da EUPS. Visando identificar as áreas de risco potencial de erosão foi elaborado o mapa de limite de tolerância às perdas de solo. Em 1966, áreas com perdas de solo acima do tolerável ocupavam 0,43% do total da área, passando para 5,86% em 1985 e para 5,43% em 1996. Todas as áreas com perdas acima do valor tolerável devem ser consideradas como em processo de degradação do solo e necessitam da implementação de práticas conservacionistas. TOLERANCE OF SOIL LOSSES IN THE ITIQUIRA RIVER BASIN, STATE OF MATO GROSSO, BRAZIL Abstract The geographic area of the present study corresponds to the basin of the Itiquira river high course (Figure 1), in the portion that extends from the tributaries of its source, in the east of the plateau Correntes/ Itiquira, in the neighbourhoods the city of Alto Garças, to the scarp of the São Jerônimo mountain range, toward the west of Itiquira, in the state of Mato Grosso, totalizing 5,361 km2. The area is placed in the eastern part of the Alto Paraguai basin, in the western portion of the Paraná Sedimentary Basin plateau. Through GIS techniques, it was possible to asses total soil losses from the Itiquira river basin, considering the years of 1966, 1985 and 1996, being based on the Universal Soil Loss Equation. Thus, in 1966 the basin lost 201,546.94 ton of soil, with an average loss of 0.37 ton/ha/year. Considering that the total area of the Itiquira river basin is of 536,100 ha, while in 1985 the soil losses had passed to 1,760,833.40 ton, with an increase of approximately 8.5 times. The average of soil losses in 1985 was of 3.28 ton/ha/year. In 1996 the basin lost 1,662,043.24 ton, with a reduction of only 9.4% in relation to 1985 but, in relation the 1966, the increase continued in the order of 8 times. The average losses per hectare in this year was in the order of 3.10 ton/ha/year (Chart 1). The map of potential of the laminar erosion for 1966 (Figure 3), shows to the highest values in small areas, situated in the northeast of the area, in Alto Garças, with values between 10 the 20 ton/ha/year and some spots in sources of the Itiquira and Ariranha rivers, with values between 1 the 5 ton/ha/year. In a general way, however, the area presents low soil loss for laminar erosion in this year, with inferior values to 1 ton/ha/year. The higher class of erosion, over 10 ton/ ha/year, occupied 2,947 ha in 1966. In the year of 1985 (Figure 4), the erosive process spread over the entire studied area, and the class of erosion over of 10 ton/ha/year, already started to occupy 78,437 ha, implying an increase of approximately 27 times in 19 years. A strong increment in the erosive process was noticed in the western part of the area, to along the BR-163 road, exactly where great areas of natural vegetation (open pasture) had been transformed in culture and pasture areas. In the north-eastern part of the area was also noticed an increment in the erosive process in agreement with the increase of culture areas and reduction of the natural areas, but it was not of so intense form as in the western portion of the area. In the year of 1996 (Figure 5), the class of erosion over of 10 ton/ha/year had diminished for a total of 53.499 ha noticing a retraction of the erosive process in the western part of the area, alongside the BR-163 road. On the other hand, it occurred a strong increment in the northern part of the area, in the neighbourhoods of the city of Alto Garças, alongside the BR-364 road and part of the MT-040 road. In a general way, in the outskirts of the city of Itiquira, in the central part of the area, it was verified an increase of the amount of zones with erosion between 0-1 ton/ha/year, passing to the immediately superior class, of 1-3 ton/ha/year ; scarce data of hydrosedimentology in the UHE Itiquira (1999), shows good agreement with the values gotten for the EUPS (Chart 2). Based on the hydric classification proposal for FAO (1967) (Chart 3), it is noticed that areas with high degree of erosion (> 50) in the analysed area are very restricted, occupying 493 ha in 1985 and 332 ha in 1996 (Chart 4). In 1996 appeared as isolated spots in the north of Itiquira and Alto Garças, however beyond limits of the Itiquira river basin. These areas require special cares in its use as agricultural areas. Aiming at identifying and indicating the areas of potential risk of erosion and that need implementation of conservation practices, it was elaborated the map of limit of tolerance to the soil losses. In 1966 (Figure 6), areas with soil losses over of the tolerable were restricted to small spots located in the eastern part of the area, occupying 0.43% of the total of the area; already in 1985 (Figure 7), this percentage passed to 5.86%, spreading for all the area; in 1996 (Figure 8) it is observed a fast reduction of the areas with soil losses over of the tolerance limit, passing 5.43% of the total of the area. All the areas with losses over of the tolerable value must be considered as risk areas and were done in these areas studies for implementation of conservation practices.